Conjugated electrospinning toward a dual conductive network Janus-shaped microfiber array film with enhanced green luminescence and high aeolotropic conduction. (8th November 2022) - Hu, Yaolin; Qi, Haina; Ma, Qianli; Yang, Liu; Shao, Hong; Sheng, Yuqi; Xie, Yunrui; Yu, Wensheng; Li, Dan; Dong, Xiangting
Abstract : Fluorescent anisotropic conductive Janus-shaped microfiber array film with a dual conductive network is designed and prepared by a conjugated electrospinning method. Abstract : In order to further promote aeolotropic conductive films (ACFs) to achieve new breakthroughs, endowing ACFs with a visual function and higher aeolotropism is a meaningful research topic. Herein, a new kind of ACF with intense aeolotropic conduction and enhanced green luminescence was constructed. A conjugated electrospinning-manufactured Janus-shaped microfibers array film (abbreviated as C-JMAF) was fabricated with a [Tb(SSA)3 (TPPO)2 /polymethylmethacrylate (PMMA)]//[polyaniline (PANI)/carbon black (CB)/PMMA] Janus-shaped microfiber as a construction block. The rational use of conjugated electrospinning to fabricate peculiar Janus-shaped microfibers could avoid the diffusion and mixture phenomenon between the two spinning liquids in the preparation process by conventional di-axial parallel electrospinning, and successfully limit the Tb complex, PANI, and CB to their respective regions to shun unfavorable reciprocal impacts. Therefore, C-JMAF demonstrated enhanced green luminescence, excellent visualization, and extremely high aeolotropic conduction. The introduction of Tb(SSA)3 (TPPO)2 guarantees C-JMAF with high luminescence, and this luminescence can be used to monitor whether C-JMAF operates normally or is out of order in darkness. Here, a dual conductive network composed of PANI and CB was first used to construct conductive block of ACFs. An obvious synergistic effect between PANI and CB was demonstrated. The aeolotropic degree of C-JMAF with the dual conductive network structure could reach 10 9, which is the highest conductivity ratio between the two vertical directions for Janus-shaped microfiber array films reported internationally so far. The dual conductive network Janus-shaped microfiber was used to construct advanced high performance ACFs, which supplies a new strategy and technical guidance for the development of novel ACFs.